Botulinum Toxin Injection with Conjunctival Microincision for the Treatment of Acute Acquired Comitant Esotropia and Its Effectiveness. (31st December 2020) - Xu, Hongjia; Sun, Weifeng; Dai, Shuying; Cheng, Yanyan; Zhao, Jing; Liu, Yuan; Wang, Juan; Wang, Ya'nan; Gao, Yu; Han, Huifang; Han, Aijun
Abstract : Purpose . To report on an improved botulinum toxin injection with conjunctival microincision for beginners, and to determine the effectiveness of botulinum toxin A (BTXA) in the treatment of patients with acute acquired comitant esotropia (AACE). Methods . Medical records of 29 AACE patients were retrospectively analyzed. BTXA was injected into the unilateral or bilateral medial rectus muscle with conjunctival microincision without electromyographic guidance. Success was defined as total horizontal deviation ≤10 prism diopters (PD) and evidence of binocular vision. Results . Twenty-nine patients were included, of whom 22 were male and 7 were female. The mean age at onset was 14.2 ± 7.4 (range, 4–34) years. The mean time from onset of AACE to injection was 18.4 ± 20.3 (range, 1–96) weeks. All patients completed at least 6 months of follow-up, and the mean follow-up after BTXA injection was 12.3 ± 4.8 months (range, 7–24 months). Neurological evaluation and brain magnetic resonance imaging (MRI) were unremarkable in all patients. The mean spherical equivalent refraction was −1.22 ± 2.85D and −0.97 ± 2.80D in the right and left eyes, respectively. Mean preinjective esotropia was 38.4 ± 18.9 PD (range, +10–+80 PD) at near and 40.2 ± 17.7 PD (range, +20–+80 PD) at far distance. The mean angle of deviation at 6 months after injection was 0.6 ± 4.1 PD (range, −3–+15 PD) at near and 3.0 ± 5.9 PD (range, 0–+20 PD) at far distance. There was significant difference in the angle of deviation at near and far fixation between pre-BTXA and post-BTXA 6 months (p < 0.001, p < 0.001, resp.). There was no significant difference in the angle of deviation at near and far fixation between post-BTXA 6 months and post-BTXA at final follow-up (p = 0.259 and 0.326, resp.). Mean stereoacuity improved from 338 to 88 arc seconds. During the follow-up period, 5 of 29 patients had recurrent esotropia. Two patients refused all further treatment, and the other 3 patients required incisional strabismus surgery. The success rates were 86.2% (25/29) at 6 months and 82.8% (24/29) at final follow-up. Conclusion . Conjunctival microincision injection of botulinum toxin is a practical and safe method for beginners to locate an extraocular muscle, which is as effective as the traditional methods. Botulinum toxin injection can be preferred as the first-line treatment for AACE patients with potential binocular vision.